2017
DOI: 10.1007/s11031-017-9619-5
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving emotion in non-social targets: The effect of trait empathy on emotional contagion through art

Abstract: This research examines the role of trait empathy in emotional contagion through non-social targets—art objects. Studies 1a and 1b showed that high- (compared to low-) empathy individuals are more likely to infer an artist’s emotions based on the emotional valence of the artwork and, as a result, are more likely to experience the respective emotions themselves. Studies 2a and 2b experimentally manipulated artists’ emotions via revealing details about their personal life. Study 3 experimentally induced positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…The result is an emotional and physiological state matching between a target and an observer (de Waal & Preston, 2017). EC and empathy are proposed to be distinct but partially overlapping constructs (de Vignemont & Singer, 2006;Luckhurst, Hatfield, & Gelvin-Smith, 2017;Stavrova & Meckel, 2017). In particular, EC can be seen as a precursor of empathy, which does not involve self-other distinction (Klimecki & Singer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The result is an emotional and physiological state matching between a target and an observer (de Waal & Preston, 2017). EC and empathy are proposed to be distinct but partially overlapping constructs (de Vignemont & Singer, 2006;Luckhurst, Hatfield, & Gelvin-Smith, 2017;Stavrova & Meckel, 2017). In particular, EC can be seen as a precursor of empathy, which does not involve self-other distinction (Klimecki & Singer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In sum, the contribution of dispositional empathy to emotions elicited by artworks is still unclear. Studies are still very few (e.g., Stavrova & Meckel, 2017), as research on fiction and empathy has been mostly concerned with how reading improves social–cognitive abilities and empathy (Kidd & Castano, 2013; Mar et al, 2011; Mar et al, 2009). We believe that further investigating the relation between reading experience, empathy and art-induced emotions can only expand this line of research.…”
Section: Discussionmentioning
confidence: 99%
“…Although the consequences (e.g., emotional responses) of these two engagement styles have not been investigated, what these results suggest is that some readers might be more inclined to empathize with fictional characters than others, perhaps due to higher trait empathy. Other studies have found that more empathetic readers are better at inferring the emotions felt by the writer while creating the text, and more prone to feeling these same emotions while reading the text (Stavrova & Meckel, 2017). These findings considered, we suggest that trait empathy is another reader characteristic worth investigating in relation to poetry-elicited emotions.…”
Section: What Kind Of Emotions Does Poetry Elicit?mentioning
confidence: 99%
“…Emotional contagion has long been recognized in epidemiology [ 31 - 33 ], literature [ 34 - 38 ], politics [ 39 ], and the arts [ 40 ]. It does not need personal (vis-à-vis) contact, as the limbic system is intended to recognize and interpret nonverbal cues of “others” via empathy processes [ 41 ].…”
Section: Discussionmentioning
confidence: 99%